Northern and Southern European grey wolf (Canis lupus) prey choice, role as the Keystone species in a scavenger community and activity pattern - APOLLONIO, Marco (Università degli studi di Sassari, 2014)
Grey wolf is an elusive predator, highly adaptable and capable of adjusting to different ecological conditions.I studied prey choice of wolf in Scandinavia and Tuscany and looked at variances between territories within the two study areas. I used analysis of scats collected during a period of nine year in Scandinavia and four years in Tuscany.I found greater habitat heterogeneity in Tuscany which leads to a more complex predator-prey structure. In Scandinavia seasonal prey type choice was more dynamic; reasons may be related to the fact that highly exploited forestry industry in Sweden disabled rich ecological diversity. The Tuscan Apennines has been depopulated as abandoned agriculture allows re-forestation and ungulate species abundance to increase.I did a movement triggered camera study of the scavenger guild in wolf territories feeding on carcasses and analysed 24 h and seasonal activity patterns. I also looked at anti-predator behavior in intra-guild members using these feeding sites. I discovered in both the diet and the camera studies that there was no avian prey in the wolf diet, nor avian scavengers at the carcass sites in Tuscany.There is a trade-off between time spent feeding and anti-predator behavior. I quantified the level of vigilance in scavenger species and compared safety investment by vigilance behavior in Tuscan and Swedish scavengers, specifically red fox and marten. I found that martens in Tuscany feed more and invests less in anti-predator behavior.